Rancang Bangun Mesin Otomatis Pencacah mini Serabut Kelapa (Mesin Cocopeat) - Arfittariah Arfittariah; Abdul Zain; Akbar Akbar (Program Studi Teknik Informatika, Fakultas Teknik. Universitas Serambi Mekkah, 2021)
Abstract — The limited land has opened up scientists' insight that in farming it is not only land that can be relied on as a planting medium. There are still other growing media, such as cocopeat. However, cocopeat engine products that are sold are very expensive, large in size and not environmentally friendly because they use gasoline or diesel engines which cause a lot of pollution in the air and produce noise when operating, therefore a cheap, quality and environmentally friendly Cocopeat engine is needed. maintenance is cheap and safe. The purpose of this study was to increase the production of cocopeat for planting media as a substitute for soil and efficient cocopeat machine which is automatic, cheap and environmentally friendly. The research method is data collection, literature study and then design with a 1 phase pK electric motor circuit design, infrared sensor, 1 channel relay module and serrations from a sharpened nail that rotates when the electric motor is run. The results obtained from the process of chopping coconut husks produce cocopeat and cocofiber to be used as planting media, which processing machines from a safe and environmentally friendly power source.Keywords: planting medium, Cocopeat, cocofiber, environmentally friendly